2021
DOI: 10.4324/9781003166771
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Federalism and Covid-19

Abstract: This comprehensive scholarly book on comparative federalism and the Covid-19 pandemic is written by some of the world's leading federal scholars and national experts.The Covid-19 pandemic presented an unprecedented emergency for countries worldwide, including all those with a federal or hybrid-federal system of government, which account for more than 40 per cent of the world's population. With case studies from 19 federal countries, this book explores the core elements of federalism that came to the fore in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Third, not all federations are equally resistant to centralization. Another study of COVID-19 in European federations found, in our reading, that while there was centralization and a focus on the head of government everywhere, Belgium and Germany were both more resistant to central coordination and decentralized more quickly; our tables suggest the same [63] .…”
Section: Discussionmentioning
confidence: 49%
“…Third, not all federations are equally resistant to centralization. Another study of COVID-19 in European federations found, in our reading, that while there was centralization and a focus on the head of government everywhere, Belgium and Germany were both more resistant to central coordination and decentralized more quickly; our tables suggest the same [63] .…”
Section: Discussionmentioning
confidence: 49%
“…However, COVID-19 poses unprecedented challenges to democratic governance (3,4). Different democracies respond to the crisis differently (5)(6)(7). In some democracies, their information advantage has not prevented epidemic outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the federal system is more conducive to solving the challenges of diverse regions, and the unitary governance system is conducive to reducing intergovernmental conflicts (17). Different federal systems also affect different crisis management in democratic countries (7). A more centralized democracy with an independent healthcare sector can respond to crises more quickly (13).…”
Section: Introductionmentioning
confidence: 99%
“…La rápida propagación de la COVID-19 supuso un gran reto para los Gobiernos de todo el mundo. En el caso de los países con sistemas compuestos o territorialmente complejos, la pandemia ha planteado desafíos especiales, ya que el control de la propagación del virus y la gestión de los recursos ha requerido de la coordinación entre Gobiernos y sectores de política pública (véase OCDE, 2020;Liu et al, 2021;Steytler, 2022;Chattopadhyay et al, 2022). Además, la pandemia ha puesto en jaque la fragmentación de los sistemas sociosanitarios de muchos países.…”
Section: Introductionunclassified